Proposta de gestão ecônomico-financeira aplicada em plantas industriais de energias renováveis a partir da biomassa: uma análise comparativa de gestão de custos entre Brasil e Espanha - Paiva, Sérgio [UNESP] (2013)
This research investigated the topic of renewable energy through a proposed method in order to trace the economic and financial viability of two industrial plants from biomass. The first, called 'sugarcane unit industrial plant' (also named as plant I in this text), located in São Paulo State, Brazil, produces not only sugar and alcohol, but also energy (mechanical, thermal and electrical), and these types of energy are produced from sugarcane bagasse. The second, called 'industrial thermal power plant' (also named as plant II), located in Castilla y León (one of the Autonomous Communities in Northern Spain), produces only thermal energy, indicated by MWh. Plant I produces energy out of forest residues from pruning pine trees. Both plants belong to Biomass Renewable Energy. The proposed method of analysis entitled as 'Proposal of Applied Economic and Financial Management in Biomass Renewable Energy' is based on Kaplan's and Anderson's (2008, 2007, 2004), Kaplan's and Cooper's (1988), Gitman's (2004); Van Horne's (1993) and Allora's et al (1995) theoretical postulates. The ...